Considerations for High-Fidelity Modeling of Unsteady Flows in a Multistage Axial Compressor - Douglas R. Matthews; Nicole L. Key (International Journal of Turbomachinery, Propulsion and Power)
This paper presents the development and validation of a high-fidelity, unsteady, computational fluid dynamics (CFD) model of the Purdue 3-Stage Axial Research Compressor. A grid convergence study assesses the spatial discretization accuracy of the single-passage, steady-state computational model. Additionally, the periodic-unsteady convergence of the unsteady signals of a multiple-passage transient blade row model was explored. Computational predictions were compared with experimental measurements to evaluate the efficacy of the various modeling decisions. Notably, transient blade row model calculations employing the Scale-Adaptive Simulation (SAS) formulation of Menter’s Shear Stress Transport (SST) turbulence model exhibited a significantly improved agreement with experimental data compared to steady-state calculations. Particularly, in conjunction with the SAS-SST turbulence model, the transient calculations significantly improved the spanwise (radial) mixing characteristics of the transient-average stagewise total temperature profiles. Spectral analyses of the transient signals compared with unsteady pressure measurements showed fundamental and second harmonic blade-passing frequency amplitudes matching within 5–7% in the embedded stage. This research underscores the importance of including accurate geometry, practical minimization of modeling assumptions using higher-fidelity physics models, comprehensive convergence assessment, and the comparison and validation of computational predictions with experimental measurements.